Childhood correlates of adult positive mental well-being in three British longitudinal studies - Wood, N; Hardy, R; Bann, D; Gale, C; Stafford, M (BMJ Publishing Group, 2020)
BACKGROUND: Previous evidence has shown how experiences within childhood, such as parenting and socioeconomic conditions, are associated later on in life with adult mental well-being. However, these studies tend to focus on childhood experiences in isolation, and fewer studies have investigated how multiple aspects of the childhood environment, including both socioeconomic and psychosocial aspects, are associated with adult positive mental well-being. Using data from three British birth cohort studies, we investigated how prospective measures of the childhood environment up to the age of 16 years were associated with midlife adult mental well-being and whether similar associations were replicated across different generations.